Analysis of Solid Medical Waste Management at Health Centers in Bengkalis District, Bengkalis Regency - Maulia, Nela Dwi; Manda Putra, Ridwan; Bayhakki, Bayhakki (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Solid medical waste management at Bengkalis District Health Centers still faces various obstacles, including limited facilities, lack of compliance with standard operating procedures, and minimal trained human resources. This study aims to analyze the condition of solid medical waste management at Bengkalis District Health Centers and formulate effective strategies in its management. The research method used was a qualitative approach with data collection through in-depth interviews and observations at Health Centers in the area. The results of the study indicate that solid medical waste management has not been running well, although the health centers have collaborated with third parties in waste management, there are still various problems such as delays in waste transportation, inappropriate storage, non-compliance with standard operating procedures (SOP), limitations in facilities and infrastructure, and health workers' awareness of the importance of waste management was also still low. The recommended strategies include increasing the capacity of health workers through training, optimizing waste management facilities, and strengthening regulations and supervision so that medical waste management can run according to established standards. The implementation of this strategy was expected to make the management of solid medical waste in health centers more efficient, safe and environmentally friendly, so that the risk of pollution can be minimized.